Effects of glyphosate exposure on western diet-induced non-alcoholic fatty liver disease in mice - Romualdo, Guilherme R. [UNESP]; Valente, Letícia Cardoso [UNESP]; dos Santos, Ana Carolina Sprocatti [UNESP]; Grandini, Núbia Alves [UNESP]; Camacho, Camila Renata Correa [UNESP]; Vinken, Mathieu; Cogliati, Bruno; Hou, De-Xing; Barbisan, Luís Fernando [UNESP] (Elsevier, 2023)
We evaluated whether glyphosate promotes western diet (WD)-induced non-alcoholic fatty liver disease (NAFLD). Male C57BL/6J mice were fed WD and received intragastrical glyphosate (0.05, 5 or 50 mg/kg) for 6 months. Glyphosate did not promote WD-induced obesity, hypercholesterolemia, glucose intolerance, hepatic steatosis, and fibrosis. Nonetheless, the higher dose (50 mg) enhanced hepatic CD68+ macrophage density, p65, TNF-α, and IL-6 protein levels. Furthermore, this dose decreased hepatic Nrf2 levels, while enhancing lipid peroxidation in the liver and adipose tissue. Hepatic transcriptome revealed that glyphosate at 50 mg upregulated 212 genes and downregulated 731 genes. Genes associated with oxidative stress and inflammation were upregulated, while key cell cycle-related genes were downregulated. Our results indicate that glyphosate exposure – in a dose within the toxicological limits - impairs hepatic inflammation/redox dynamics in a NAFLD microenvironment.
Keywords: C57BL/6J mice; Glyphosate; Inflammation; Non-alcoholic fatty liver disease; Oxidative stress